Indonesia DAMPAK PENGGUNAAN AI (ARTIFICIAL INTELLIGENCE) TERHADAP CARA BERFIKIR KRITIS SISWA KELAS 8 SMP NEGERI 1 BAURENO: Studi Kasus Penggunaan AI Kepada Siswa Kelas VIII SMP Negeri 1 Baureno - Isnadia Fajriati; Sanita Carolina Sasea (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2026)
This study examines the impact of Artificial Intelligence (AI) use on the critical thinking skills of 8th-grade students at SMP Negeri 1 Baureno in Social Studies, to understand the gap between students who use AI analytically and those who rely on AI as an instant answer source in the rapidly evolving era of educational digitalization. The study aims to analyze differences in students' interaction patterns with AI and reveal their impact on the achievement of critical thinking indicators in the learning process. A descriptive qualitative method was employed, with data collected through in-depth interviews with the Social Studies teacher, students from classes 8B and 8F, participatory classroom observation, and documentation. The main findings reveal a significant contrast between the two classes in their use of AI. Students in class 8B used AI selectively and analytically, successfully meeting all four critical thinking indicators according to Ennis, R. H. (1996). Meanwhile, students in class 8F relied on instant answers provided by AI, resulting in stagnation of their critical reasoning abilities. This study confirms that AI is not the cause of weakened critical thinking skills; rather, it is the pattern of use adopted by students that determines whether AI has a positive or negative impact on them. Practical implications include recommendations for integrated school policies and strengthening the role of teachers as active facilitators in guiding AI use. Although limited to a single school, data source triangulation ensures the validity of the findings, contributing to the development of more critical and directed technology-based learning strategies.